Komponen Fizikal Pembinaan Kolej Kediaman Lestari di Universiti Awam Malaysia: Tinjauan Literatur: Physical Components of Sustainable Residential Colleges Construction in Public University Malaysia: Literature Review - Buyung, Mohd Reduan; Shafii, Haryati (GEOGRAFI, 2018)
This article is a preliminary study to build a sustainable residential college in the future. The main problem in this study is the absence of a complete guideline in developing a comfortable and conducive residential college. The impact will result in weaknesses and disadvantages in the provision of facilities at residential colleges that ultimately lead to discomfort in occupants. The sustainability of residential colleges will also be affected and in general will contribute to the deterioration of the quality of life of the occupants. This article is to identify the physical components in the architecture that can affect the construction of a sustainable residential college. The methodology of the study is based on literature reviews on components such as construction sites, buildings, accessibility, disabled facilities, security, landscaping and recreation areas. The results of the study show that each component that has been studied has influence and impact on the residential college and its occupants. The findings in this study will be used to assist in the study of residential colleges to the concept of a sustainable residential college that provides complete, comfortable and conducive facilities thus leading to the improvement in the quality of life for residential colleges in Malaysian public universities.